A Review of Cybersecurity Framework Implementation for Retail Industry-Challenges and Recommendation - Eleonora Anggi Ardhaninggar; Kallamulah Ramli (PT ARRUS Intelektual Indonesia, 2024)
Efforts to improve services by opening online data access to customers have become straightforward targets for cybercrime. Unfortunately, the researchers' findings reveal that there is presently no cybersecurity framework that completely aligns with the fundamental principles of the retail industry. This paper then analyzes the deployment of cybersecurity frameworks across various industrial sectors to determine which framework—or combination of frameworks—best aligns with the fundamental values of the retail industry. We compare the essential points of each cybersecurity framework with the TWOS Matrix, which represents the core values of the retail industry. We suggest NIST CSF, ISO/IEC 27001:2022, and Essential Eight as the best combination of cybersecurity frameworks for the retail industry. Therefore, the comparative analysis results recommend RCF as a novel framework suitable for implementation in the retail industry.